Hyalomma dromedarii infesting camels in Hail Province, Saudi Arabia, carry antimicrobial resistant bacteria - Aljasham, Alanoud T.; Raghunandanan, Sajith; Farzan, Raed; Abdulwahed, Abdulhadi M.; Aneesh, Embalil Mathachan; Alharbi, Sumiyaa; Shukri, Yusra; Alshammari, Mohammed; Alanazi, Fuad (Frontiers in Veterinary Science, 2025)
Ticks are known vectors of various pathogens and are increasingly recognized as carriers of antimicrobial-resistant (AMR) bacteria. However, the role of camel ticks in AMR transmission remains poorly understood. In this study, we investigated bacteria isolated from Hyalomma dromedarii hard ticks collected from dromedary camels in Hail Province, Saudi Arabia, and assessed their AMR profiles. A total of 57 ticks were collected, yielding 29 bacterial isolates. The majority (79%; 23/29) were Gram-negative bacteria, primarily Enterobacter cloacae complex (n = 21) and Pseudomonas putida (n = 2). Gram-positive isolates (21%; 6/29) included Staphylococcus sciuri (n = 4) and Staphylococcus xylosus (n = 2). All Gram-negative isolates were resistant to cefazolin, 91% to amoxicillin/clavulanic acid, and 8.7% to trimethoprim/sulfamethoxazole, while remaining susceptible to higher-generation cephalosporins, carbapenems, and aminoglycosides. Among Gram-positive isolates, resistance to fusidic acid was universal, with occasional resistance to benzylpenicillin (33%) and erythromycin (17%). No multidrug resistance across three or more antibiotic classes was observed. These findings highlight the presence of clinically relevant AMR bacteria in camel ticks and underscore the need for targeted AMR surveillance in arid livestock regions. Such efforts are critical to understanding and mitigating AMR risks within the animal–human–environment interface of the One Health framework.